The global landscape of poverty, food insecurity, and malnutrition, and its implications for agricultural development strategies - Headey, Derek D. (International Food Policy Research Institute, 2013)
For many years poverty reduction was the overarching welfare objective of a wide range of development institutions and programs, particularly in the context of agricultural development. Yet in recent years the development community has increasingly set for itself more specific welfare objectives by distinguishing between monetary poverty, food security, nutrition and, most recently, resilience. This paper first outlines a basic framework for thinking about the relationships between these different concepts, and then explores the empirical relationships among different indicators of these concepts, and some of their potential determinants.